Effect of Petroleum Products on Liver Function among Petroleum Filling Workers Stations in El-Obied City –Sudan - Elsukar, Akram Awadalla; Ahmed, Nizar; Khaleel, Manahil (Journal of medical and pharmaceutical sciences, 2018)
Background: Lengthened exposure to petrol has been shown to be a significant health risk, especially for liver, renal, and circulatory, reproductive and immuneystems. Objective: This study aimed to investigate the hepatotoxic effects of petroleum products on filling workers stations after chronic exposure more than one year on their liver function tests. Patients, Materials & Methods: A cross sectional study conducted during the period from October 2015 to August 2016 to determine the plasma levels of liver function tests of filling workers stations in El-Obied city.Thirty Seven filling workers were selected as a test group in comparison to 30 apparently healthy volunteers as control group matched for age and sex to the tested group. Blood specimens were collected from both groups, and the plasma levels of total protein, albumin, total bilirubin (direct, Indirect) and ALT were measured using a spectrophotometric technique. Results: The study revealed to significant raised levels of the plasma albumin (4.7 ± 0.8 g/dl) and ALT (17.6 ± 5.1u/l) of the test group when compared with the control group whereas no significant different in the plasma levels of total protein (7.5 ± 0.6 g/dl) ,total bilirubin (0.7 ± 0.3 mg/dl),direct bilirubin(0.3±0.1 mg/dl) and indirect bilirubin (0.3±0.2 mg/dl) of the test group when compared with the control group(7.3±0.7 g/dl, 0.8±0.4mg/dl, 0.3±0.2 mg/dl and 0.4±0.3 mg/dl respectively). Conclusion: This study indicates that; liver function impairment and hepatotoxicity among filling station workers may attribute to prolong exposure to petroleum product, therefore upgrading of working condition and regular checkup is recommended.
Keywords: North Kordofan state; Filling station petroleum; Total protein; Albumin